(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Current study demonstrated that 14.58% of isolated E. coli which positive for each of Omp -A, IMP- A, NDM- A and Fim- H genes were resistant to carbapenem and the study showed that 30.51% of E. coli isolates with KPC were resistant to carbapenem while other E. coli isolates with negative all genes were resistant to carbapenem , so the Percentage as 72.92% of isolated E. coli were positive for each of Omp – A, IMP – A, NDM- A and Fim – H genes were occurred in females compared with 27.02% occurred in males and 40% of isolated E. coli with positive for KPC gene were in females with UTI. as well as 10, 50% of isolated E. coli were positive for each of Omp- A, IMP - A, NDM- A and Fim - H genes were occurred in the age group 15-24 year and no isolate were form patients above 54 year. the highest mean levels IL-6 and IL-17 was recorded in UTI patients infected with E. coli positive for each of Omp- A , IMP- A , NDM- A and Fim- H comparing with patients infected with E. coli negative to these genes. Conclusion Carbapenem-resistant E. coli correlated with founded each of genes ( Omp -A, IMP- A, NDM- A and Fim- H ) , whilst highest correlated between Carbapenem-resistant E. coli with KPC.so sera levels of both interleukins (IL-6 and IL-17) were recorded in UTI patients infected with E. coli positive for each genes ( Omp- A , IMP- A , NDM- A and Fim- H ) comparing with patients infected with E. coli negative to these genes.